A review of the safety of MRI in cochlear implant patients with retained magnets. Issue 12 (December 2019) - Srinivasan, R.; So, C.W.; Amin, N.; Jaikaransingh, D.; D'Arco, F.; Nash, R.
Abstract : The number of patients with cochlear implants (CIs) is increasing due to expanding indications, and improving CI services. Furthermore, as the use of imaging increases in clinical medicine, it is increasingly likely that patients with CIs will require a magnetic resonance imaging (MRI) examination during their lifetime. Therefore it is important that clinicians are aware of the safety aspects and manufacturer recommendations for CI patients with retained magnets. This article summarises guidelines from all major CI manufacturers and reviews the published literature on the safety of MRI in CI patients with magnets in situ . The most commonly reported complication of MRI in CI patients was pain. Other significant complications included magnet displacement, depolarisation, and polarity reversal. Artefacts caused by the CI remain an issue, but may be reduced by the use of specific sequences. Manufacturer recommendations should be followed to reduce the risk of complications, although complications may occur even when guidelines are followed. For this reason, the indication for imaging these patients should be reviewed, and patients should be appropriately counselled and consented.